2020
DOI: 10.1017/s1751731120000518
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spray-dried rumen fluid supplementation on performance, blood metabolites and cytokines in suckling Holstein calves

Abstract: Rumen fluid from slaughtered animals is one of the wastes of slaughterhouses released to the environment that, due to its high nitrogen and phosphorus contents, can lead to soil and groundwater pollution. Meanwhile, it contains ruminal microbes and some bioactive compounds such as enzymes, minerals, vitamins and organic acids. This study was designed to examine the potential of rumen fluid as a feed additive. Therefore, the effects of spray-dried rumen fluid (SDR) with 1% maltodextrin on the performance, blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…A previous study found that multi-strain probiotic increased serum CHOL in neonatal dairy calves (Guo et al, 2022), which was similar to our study. However, a low blood concentration of CHOL was also observed in a previous study with spray-dried ruminal fluid inoculation (Rezai Sarteshnizi et al, 2020). Combined with the greater HDL blood content in RF relative to CON, the greater CHOL might be helpful in preventing lipid peroxidation and stimulating the synthesis of anti-inflammatory cytokines (such as interleukin-10) (Mertens and Holvoet, 2001).…”
Section: Effect Of Ruminal Fluid Inoculation On Blood Biochemical Par...mentioning
confidence: 69%
“…A previous study found that multi-strain probiotic increased serum CHOL in neonatal dairy calves (Guo et al, 2022), which was similar to our study. However, a low blood concentration of CHOL was also observed in a previous study with spray-dried ruminal fluid inoculation (Rezai Sarteshnizi et al, 2020). Combined with the greater HDL blood content in RF relative to CON, the greater CHOL might be helpful in preventing lipid peroxidation and stimulating the synthesis of anti-inflammatory cytokines (such as interleukin-10) (Mertens and Holvoet, 2001).…”
Section: Effect Of Ruminal Fluid Inoculation On Blood Biochemical Par...mentioning
confidence: 69%
“…On the other hand, serum interferon-γ concentration at day 20 was influenced by SDR supplementation, with the highest value recorded for SDR 1.5-fed calves. In conclusion, the incorporation of SDR with 1% maltodextrin in the diet of suckling dairy calves had positive effects on stimulating the calves' immune system [16] .…”
Section: Ensiling Using Whole Bloodmentioning
confidence: 83%
“…The immune systems of suckling dairy calves were improved by spray-dried rumen fluid containing 1% maltodextrin, as seen by lower interleukin-6 blood concentrations. 111 These findings suggest that providing exogenous rumen fluid to young ruminants enhances weight gain while also altering feed health, immunity, and digestibility. 112…”
Section: Rumen Transfaunationmentioning
confidence: 95%